“If that would have lessened my symptoms, that would have been great...”: a qualitative study about the acceptability of tecovirimat as treatment for mpox - Sara Paparini; Rosalie Hayes; Benjamin Weil; Will Nutland; Ismael Maatouk; Teodora Wi; Chloe M. Orkin; Rosamund Lewis (BMC Medicine)
Abstract Background Tecovirimat, an antiviral treatment for smallpox, was approved as a treatment for mpox by the European Medicines Agency in January 2022. Approval was granted under “exceptional circumstances” based on effectiveness found in pre-clinical challenge studies in animals and safety studies in humans showing minimal side effects. As clinical efficacy studies are still ongoing, there is currently limited information with regard to the acceptability of tecovirimat to treat mpox. The aim of this study is to understand prospective acceptability of use of tecovirimat as treatment for mpox. Methods A co-produced, qualitative, focus group study design was conducted with a theoretically informed sample of people from communities at higher risk and with experience of mpox illness. Thirteen participants took part: all self-identified as cisgender male, 1 self-identified as Black British, 1 as British Asian, 5 as White, 3 as White British, 3 as White Other. Inclusion criteria were as follows: experience of mpox illness; age 18 and over; living in the United Kingdom (UK); living in the UK during 2022 mpox outbreak. Focus groups were recorded, transcribed and thematically analysed using a combination inductive and deductive coding informed by the Treatment Acceptability Framework. Results Very few participants were aware of tecovirimat as a treatment option and none were offered it during their mpox illness. Key factors influencing acceptability found in this study were as follows: levels of trust in medicine; level of information; provider communication approach; quality of experience of mpox care. Marginalised communities at highest risk of mpox may have prior experience of structural discrimination which can greatly influence treatment acceptability. Conclusions This exploratory study suggest that offering tecovirimat (or comparable emergency-licensed treatments) to people with mpox is acceptable, although uptake will depend on knowledge of mpox treatment options, trust in medicine and medical professionals and provision of relevant information and choice. To increase acceptability of such treatments, clinicians should ensure patients are aware of mpox symptom management options, including pain relief; acknowledge and address patient concerns upfront and within the context of non-stigmatising care; and communicate offers in a consistent and supportive manner in line with locally approved eligibility criteria and protocols at the time.